Avaliação de impactos ambientais em trilhas de caminhada: incentivando autonomia e sustentabilidade - Kist, Thaís Cristina (2019)
Due to overexploitation of natural environments, sustainable strategies that bring man closer to nature are needed. Ecotourism is the fastest growing tourism perspective in natural environments worldwide, promoting numerous social, cultural, economic and ecological benefits. However, the excessive performance of such activities may have impacts on the ecosystem, consequently affecting the survival of species, animals and plants. Thus, this research aims to provide a tool for assessing anthropogenic impacts for walking trails, which are viable for use, accessible and easy to understand for all manager profiles, thus contributing to the management and sustainability of environments. natural. The instrument elaborated by the researcher, contains social, physical and biological aspects distributed in 19 indicators. To evaluate the instrument, 10 areas / locations were selected with the presence of a manager. At the time, the person responsible for each trail area was interviewed, aiming to observe its profile. Subsequently, the instrument was applied individually in each of the areas by the respective managers and researcher who used only the evaluation instrument and a measuring tape to standardize the measurements between the points evaluated throughout the trail length, observing at each stopping point those of the 19 indicators. The results of the measurements were then analyzed by means of a statistical test with the intention of observing the parity between evaluations and thus proving the efficiency of the instrument in identifying environmental impacts. During the application of the instrument on the trails, some doubts were observed by those responsible, thus seeking greater autonomy by the managers, some of the indicators were adjusted. It is pertinent to emphasize that the instrument may be appropriate to the needs and particularities of the area / place of environmental assessment with the commitment to assist all managers and responsible persons in identifying the impacts of walking trails independently, valuing the sustainability of natural environments.